(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2022)
Every new generation of students are having difficulties with learning mathematical subjects. The success in Mathematics is getting lower and lower, not only in Macedonia but also on global level. Mathematical materials that contain only problems with solution without their visual representation are hardly acceptable for many students. So, visualization play an important role in the process of teaching mathematics subjects. In this paper, we will present the solution of examples of plane equation and by using free software, visualization of that solution is made. For solving several examples, we are going to use the Computer Algebra System (CAS) in GeoGebra.